Deletion of the E3 ubiquitin ligase, Parkin, exacerbates chronic alcohol intake‐induced cardiomyopathy through an Ambra1‐dependent mechanism. (20th January 2021) - Yang, Mingjie; Wang, Shuyi; Fu, Shouzhi; Wu, Ne N.; Xu, Xihui; Sun, Shiqun; Zhang, Yingmei; Ren, Jun
Abstract : Background and Purpose: Chronic alcohol consumption contributes to contractile dysfunction and unfavourable geometric changes in myocardium, accompanied by altered autophagy and disturbed mitochondrial homeostasis. The E3 ubiquitin ligase Parkin encoded by PARK2 gene maintains a fundamental role in regulating mitophagy and mitochondrial homeostasis, although little is known of its role in the aetiology of alcoholic cardiomyopathy. Here we assessed the effects of Parkin deletion in chronic alcohol‐evoked cardiotoxicity. Experimental Approach: Following alcohol (4%) or control diet intake for 8 weeks, adult male wild‐type (WT) and PARK2 knockout (Parkin −/− ) mice were examined using echocardiography. Cardiomyocyte mechanical properties, morphology of myocardium, and mitochondrial damage were also evaluated. Autophagy and mitophagy levels were assessed by LC3B and GFP‐LC3 puncta, and lysosome‐dependent autophagic flux was scrutinized using GFP‐mRFP‐LC3 puncta and Bafilomycin A1 treatment. Key Results: Chronic alcohol exposure provoked unfavourable geometric changes in myocardium and led to mitochondrial dysfunction and cardiac contractile defects, effects further exacerbated by Parkin knockout. Chronic alcohol exposure provoked autophagy and PINK1/Parkin‐mediated mitophagy without affecting lysosome‐dependent autophagic flux, the effects of which were diminished by Parkin deletion. Parkin adenovirus infection in neonatal rat cardiomyocytes further increased autophagy and protected against alcohol‐induced myocardial injury, effects blocked by siRNA for Ambra1 (Autophagy and Beclin1 regulator 1). Immunofluorescence staining and co‐immunoprecipitation assays showed interactions between Parkin and Ambra1. Conclusions and Implications: Parkin was essential for cardiac homeostasis in alcohol challenge, accompanied by increased autophagy/mitophagy and maintenance of mitochondrial integrity through its interaction with Ambra1.